Court-involved African American males and social capital within Chicago public schools - Harden, Troy (2010)
This qualitative study explores how eleven court-involved African American males in Chicago Public Schools gain entry and access into mainstream society via schooling, exploring their choices, interactions and networks in the context of schooling, and how they develop trust or the lack thereof in the educational process. Five themes emerged from interviews of the eleven young men, including school engagement, neighborhood bonds, school exclusion, purgatory and social capital reconceptualized. The young men in this study reported their trajectories associated with schooling, including how they were often “pushed out”, in part by their own behavior and attitude towards schools, and school attitudes towards them. An alienation process occurred within the educational context for them, and they relied on community supports to reinforce their sense of self and belonging. Findings suggest that any analysis of social capital for these youth should include their social networks and the structural factors that influence their educational histories and choices, including neighborhood influences, as well educational policies and procedures that limit connection for them. This study informs urban researchers and practitioners on challenges that these youth encounter, and methods and ways to engage them in public education and beyond